Inovasi Pengembangan Bahan Ajar Kewirausahaan Berbasis Learning Management System di Politeknik Pelayaran Sumatera Barat - Nazarwin, Nazarwin; Kurniawan, Edi; Kurniawan, M. (PAKAR Pendidikan, 2025)
This study aimed to develop an entrepreneurship teaching module utilizing a Learning Management System (LMS) to enhance the learning process at the Politeknik Pelayaran Sumatera Barat. The module was designed using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. The research involved 72 students from the Marine Transportation program in the odd semester of the 2024/2025 academic year. Material and media experts conducted validation using observation sheets and questionnaires. The findings indicated that the LMS-based module achieved excellent validity, with an average expert validation score of 91.2%.Furthermore, students' responses regarding usability, ease of use, and user satisfaction were categorized as "very good," with an average score of 89.7%. The module enhanced learning flexibility and student engagement through interactive and relevant content like e-business planning and business feasibility studies. This module is expected to improve the quality of entrepreneurship education and better prepare students to face the challenges of the business world. Future research could explore integrating AI and AR technologies to enrich the learning experience and conduct longitudinal evaluations to assess its impact on learning outcomes and skill development.